Evaluation of the Electromagnetic Power Absorption in Humans Exposed to Plane Waves: The Effect of Breathing Activity - Marta Cavagnaro; Erika Pittella; Stefano Pisa (International Journal of Antennas and Propagation)
The safety aspects of the exposure of people to uniform plane waves in the frequency range from 900 MHz to 5 GHz are analyzed. Starting from a human body model available in the literature, representing a man in resting state, two new anatomical models are considered, representing different phases of the respiratory activity: tidal breath and deep breath. These models have been used to evaluate the whole body Specific Absorption Rate (SAR) and the 10-g averaged and 1-g averaged SAR. The analysis is performed using a parallel implementation of the finite difference time domain method. A uniform plane wave, with vertical polarization, is used as an incident field since this is the canonical exposure situation used in safety guidelines. Results show that if the incident electromagnetic field is compliant with the reference levels promulgated by the International Commission on Non-Ionizing Radiation Protection and by IEEE, the computed SAR values are lower than the corresponding basic restrictions, as expected. On the other side, when the Federal Communications Commission reference levels are considered, 1-g SAR values exceeding the basic restrictions for exposure at 4 GHz and above are obtained. Furthermore, results show that the whole body SAR values increase passing from the resting state model to the deep breath model, for all the considered frequencies.